The Effect of Price and Product Quality on Purchase Decisions with Brand Image as an Intervening Variable in The Lahat Coffee Monologue Product - Ade Tiara Febrina; Ahmad Maulana; Aslamia Rosa (Journal Research of Social Science, Economics, and Management, 2025)
The coffee shop industry in Indonesia has experienced rapid growth in recent years, with coffee becoming a staple beverage among diverse consumer groups. Monolog Coffee, located in Lahat Regency, represents a modern coffee shop that adopts both online and offline sales models. This research aims to analyze the influence of price and product quality on purchasing decisions, with brand image as an intervening variable. Using a quantitative approach and Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method, this study surveyed 100 Monolog Coffee consumers through questionnaires. The results reveal that price and product quality significantly affect brand image. Furthermore, price has a significant impact on purchasing decisions, while product quality does not show a direct influence on purchase decisions. Notably, brand image significantly mediates the relationship between the independent variables and purchasing decisions. These findings suggest that Monolog Coffee’s efforts to enhance its brand image through pricing strategy and product quality are effective in shaping customer behavior. The implication of this research is that small and medium-sized enterprises (SMEs) in the coffee industry should prioritize building a strong brand image as a strategic mediator to drive consumer loyalty and purchasing decisions. Future studies are encouraged to explore additional mediators such as customer satisfaction or digital engagement to deepen the understanding of consumer behavior in the coffee shop sector.